Towards the Improvement of Hydrotreatment Catalysts through the Encapsulation of Heteropolyoxometalates inside the Framework of SBA‐15 Silica. Issue 2 (2nd January 2014) - Silva, Susana; Chaumonnot, Alexandra; Bonduelle‐Skrzypczak, Audrey; Lefebvre, Frédéric; Loridant, Stéphane; Dufaud, Véronique
Abstract In the context of the search for higher performance hydrodesulfurization catalysts, materials made by a novel method of immobilizing heteropolyoxometalates on mesoporous oxides were compared to those derived by incipient wetness impregnation for the hydrogenation of toluene. The catalysts prepared by the one‐pot encapsulation of HPMo into the walls of SBA‐15 silica were found to be significantly more active for the reaction.